2018
DOI: 10.4103/ijmpo.ijmpo_61_17
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs and Clinical Outcomes among Men with Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) have shown properties of inhibiting the progression of prostate cancer (PCa) in preclinical studies. However, epidemiological studies yield mixed results on the effectiveness of NSAIDs in PCa. Objective: The objective of this study was to determine the effect of NSAID use on clinical outcomes in PCa using systematic review and meta-analysis. Methods: Original articles published until the 1st week of Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Many studies had investigated prediagnostic and postdiagnostic aspirin exposure with respect to mortality risk among PCa patients, with inconsistent results. The meta-analysis reported by Thakker et al [30] had analyzed the association between aspirin exposure and mortality risk; they used the data published before 2016 and showed an insignificant outcome with substantial heterogeneity. They concluded that aspirin exposure was not associated with ACM and PCSM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies had investigated prediagnostic and postdiagnostic aspirin exposure with respect to mortality risk among PCa patients, with inconsistent results. The meta-analysis reported by Thakker et al [30] had analyzed the association between aspirin exposure and mortality risk; they used the data published before 2016 and showed an insignificant outcome with substantial heterogeneity. They concluded that aspirin exposure was not associated with ACM and PCSM.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis had analyzed the association between aspirin exposure and mortality risk among PCa patients with an insignificant outcome [30]. This analysis used data published before 2016.…”
Section: Introductionmentioning
confidence: 99%